Francisco de Osuna's Norte de Los Estados in Modernized Spanish A Practical Guide to Conjugal Life in Sixteenth-Century Europe. - Bultman, Dana (Foundations Ser., 2019)
The first modern edition in Spanish of friar Francisco de Osuna's candid manual for lay life, Norte de los estados (North Star), with a comprehensive introduction in English.